Heutagogy and Lifelong Learning: A Review of Heutagogical Practice and Self-Determined Learning - Blaschke, Lisa Marie (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2012)
Heutagogy, a form of self-determined learning with practices and principles rooted in andragogy, has recently resurfaced as a learning approach after a decade of limited attention. In a heutagogical approach to teaching and learning, learners are highly autonomous and self-determined and emphasis is placed on development of learner capacity and capability with the goal of producing learners who are well-prepared for the complexities of today’s workplace. The approach has been proposed as a theory for applying to emerging technologies in distance education and for guiding distance education practice and the ways in which distance educators develop and deliver instruction using newer technologies such as social media. The renewed interest in heutagogy is partially due to the ubiquitousness of Web 2.0, and the affordances provided by the technology. With its learner-centered design, Web 2.0 offers an environment that supports a heutagogical approach, most importantly by supporting development of learner-generated content and learner self-directedness in information discovery and in defining the learning path. Based on an extensive review of the current literature and research, this article defines and discusses the concepts of andragogy and heutagogy and describes the role of Web 2.0 in supporting a heutagogical learning approach. Examples of institutional programs that have incorporated heutagogical approaches are also presented; based on these examples and research results, course design elements that are characteristic of heutagogy are identified. The article provides a basis for discussion and research into heutagogy as a theory for guiding the use of new technologies in distance education.